A mixed-methods systematic review of suicide prevention interventions involving multisectoral collaborations - Tania Pearce; Myfanwy Maple; Sarah Wayland; Kathy McKay; Alan Woodward; Anna Brooks; Anthony Shakeshaft (BMC, 2022)
Abstract Background Governments and third-sector organizations (TSOs) require support to reduce suicide mortality through funding of suicide prevention services and innovative research. One way is for researchers to engage individuals and services in multisectoral collaborations, to collaboratively design, develop and test suicide prevention services and programmes. However, despite widespread support, to date, it remains unclear as to the extent to which stakeholders are being included in the research process, or if they are, how these partnerships occur in practice. To address this gap, the authors conducted a systematic review with the aim of identifying evidence of multisectoral collaborations within the field of suicide prevention, the types of stakeholders involved and their level of involvement. Methods The authors conducted a strategic PRISMA-compliant search of five electronic databases to retrieve literature published between January 2008 and July 2021. Hand-searching of reference lists of key systematic reviews was also completed. Of the 7937 papers retrieved, 16 papers finally met the inclusion criteria. Because of data heterogeneity, no meta-analysis was performed; however, the methodological quality of the included studies was assessed. Results Only one paper included engagement of stakeholders across the research cycle (co-ideation, co-design, co-implementation and co-evaluation). Most stakeholders were represented by citizens or communities, with only a small number of TSOs involved in multisectoral collaborations. Stakeholder level of involvement focused on the co-design or co-evaluation stage. Conclusion This review revealed a lack of evidence of multisectoral collaborations being established between researchers and stakeholders in the field of suicide prevention research, even while such practice is being espoused in government policies and funding guidelines. Of the evidence that is available, there is a lack of quality studies documenting the collaborative research process. Also, results showed that the inclusion of co-researchers from communities or organizations is defined as co-creation, but further analysis revealed that collaboration was not consistent across the duration of projects. Researchers and practitioners should consider issues of power and equity in multisectoral collaborations and encourage increased engagement with TSOs, to rigorously research and evaluate suicide prevention services.